Sonic hedgehog, Wnt, and brain‐derived neurotrophic factor cell signaling pathway crosstalk: potential therapy for depression. Issue 1 (20th June 2017) - Tayyab, Mohd; Shahi, Mehdi H.; Farheen, Shirin; Mariyath, Mubeena P.M.; Khanam, Nabeela; Castresana, Javier S.; Hossain, M. Mobarak
Abstract: There are various theories to explain the pathophysiology of depression and support its diagnosis and treatment. The roles of monoamines, brain‐derived neurotrophic factor (BDNF), and Wnt signaling are well researched, but sonic hedgehog (Shh) signaling and its downstream transcription factor Gli1 are not well studied in depression. Shh signaling plays a fundamental role in embryonic development and adult hippocampal neurogenesis and also involved in the growth of cancer. In this article, we summarize the evidence for the Shh signaling pathway in depression and the potential crosstalk of Shh with Wnt and BDNF. Antidepressants are known to upregulate the adult hippocampal neurogenesis to treat depression. Shh plays an important role in adult hippocampal neurogenesis, and its downstream signaling components regulate the synthesis of Wnt proteins. Moreover, the expression of Gli1 and Smo is downregulated in depression. BDNF and Wnt signaling are also regulated by various available antidepressants, so there is the possibility that Shh may be involved in the pathophysiology of depression. Therefore, the crosstalk between the Shh, Wnt, and BDNF signaling pathways is being discussed to identify the potential targets. Specifically, the potential role of the Shh signaling pathway in depression is explored as a new target for better therapies for depression.